Control of the process of thermal and humidity treatment of construction materials - Kolisnyk, O. P.; Kots, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The system of thermal and humidity treatment control of construction materials, which is based on the obtained mathematical models of the technological process of construction materials manufacturing and allows to carry out the quality control is suggested. The technological mode of thermal and humidity treatment using the aerodynamic heater of ring-type is proposed . Block-diagram of the algorithm of thermal treatment technological modes control is constructed.